KELUARGA SEHAT DALAM PERSPEKTIF ISLAM - Zaenal Abidin (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2012)
The essence of a healthy life is a state in which a human being has a goodphysiological, psychological, social, and spiritual condition both as an individual and asocial being. With such a condition, a person can perform a tough personality, a highmotivation and expectation, and a stable life to achieve a success in his life.Moreover, when a healthy life is attained, a Muslim individual is expected to be ahard worker, creative, innovative, and productive in his life. To realize such a condition inMuslim society, it should be started from a family. Parents play an important role infacilitating their children to achieve a healthy life by guiding the children and plantingIslamic values on them.